Immunoglobulin G4-related disease preceded by lung involvement: A case report. Issue 24 (June 2017) - Abo, Miki; Takato, Hazuki; Watanabe, Satoshi; Kase, Kazumasa; Sakai, Tamami; Koba, Hayato; Hara, Johsuke; Sone, Takashi; Kimura, Hideharu; Kasahara, Kazuo
Abstract: Rationale: Immunoglobulin G4-related disease (IgG4-RD) is a systemic condition involving various organs and vessels including the pancreas, bile duct, salivary glands, periorbital tissues, kidneys, lungs, lymph nodes, meninges, and aorta. Recently, some cases of IgG4-RD have been reported, in which only pulmonary lesions were present. It is not known whether IgG4-RD can be diagnosed on the basis of pulmonary lesions only, because increases in serum IgG4 levels and infiltration of IgG4-positive plasma cells into the lung tissue also occur in other inflammatory conditions. A case of IgG-RD that was followed-up for 7 years after onset is described. Patient concerns: Initially, only pulmonary lesions were present; however, other lesions in the submandibular glands, pancreas, periarterial region, and other areas occurred over time, with a gradual increase in serum IgG4 levels. Diagnoses, interventions, and outcomes: Histopathology results from the patient's submandibular gland confirmed the diagnosis of IgG4-RD. Following diagnosis, the patient was treated with corticosteroids immediately, and his symptoms disappeared rapidly. Lessons: Because other diseases, including malignancies, mimic IgG4-RD in clinical and histopathological features, an absolute diagnosis is necessary to avoid missing the presence of underlying diseases. This case more provides insight into the clinical pathology of IgG4-RD.